Rancang bangun aplikasi it helpdesk berbasis web pada PT. Sinergi Adimitra Jaya - Ruseno, Ndaru; Mulyana, Nana; Kurniawan, Sigit (Yayasan Bina Internusa Mabarindo, 2024)
PT.Sinergi Adimitra Jaya is a company engaged in manufacturing diapers. The company's helpdesk is the first part that users contact when they have problems or questions related to IT. IT staff have problems when recording information on a form. The absence of an application to store information from forms into databases makes it difficult to trace the information data when needed. IT staff are also constrained in terms of assignments. Because the assignment is carried out when there is an incoming problem, it has not been adjusted to the problem category and IT expertise. Based on these problems, an application is needed so that users can convey their problems to IT, and can see the status of their handling. In addition, an application was also created for the process of dividing tasks when handling problems or work. For the design method, UML is used as visual modeling. The SWOT method is used to determine the problem analysis. The data collection method used in this study uses field studies in the form of interviews and observations and also literature studies from journals related to the problems discussed. With the creation of this system, it can improve the IT helpdesk service process to be more structured so that it makes it easier for users to submit problem complaints to IT and make it easier for IT in terms of assignments.